2019
DOI: 10.1787/b11a6e8f-en
|View full text |Cite
|
Sign up to set email alerts
|

Improving Healthcare Quality in Europe

Abstract: The designations employed and the presentation of the material in this publication do not imply the expression of any opinion whatsoever on the part of the European Observatory on Health Systems and Policies concerning the legal status of any country, territory, city or area or of its authorities, or concerning the delimitation of its frontiers or boundaries. Indeed, this document, as well as any data and map included herein, is without prejudice to the status of or sovereignty over any territory, to the delim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 426 publications
0
6
0
Order By: Relevance
“…Overall, the data showed no differences between accommodation types or favoured shared accommodation. Only the OECD study indicated reduced risk of falls in single rooms, 41 but the quality of this study was deemed to be very low due to reporting very few details of the research. Significantly lower rates of falls were seen in multibed accommodation in two studies.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, the data showed no differences between accommodation types or favoured shared accommodation. Only the OECD study indicated reduced risk of falls in single rooms, 41 but the quality of this study was deemed to be very low due to reporting very few details of the research. Significantly lower rates of falls were seen in multibed accommodation in two studies.…”
Section: Resultsmentioning
confidence: 99%
“…However, the organization should note that CPs implementation required a number of resources once it is recommended as an active process [3]. An active process requires maximum healthcare inputs and supports from managers and healthcare professionals to remove associated resistance from the CPs implementation.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical pathways (CPs) can be used as tool to guide evidence-based healthcare [3]. It reserves an integrated service plan to deliver clinical processes, interventions, and treatments with measurable outcomes in a timely fashion [4].…”
Section: Introductionmentioning
confidence: 99%
“…The selection of countries was designed to capture approaches from both similar and different health systems, looking from Eastern Europe to Western models. First, we included EU Member States with similar social health insurance systems covering health services: Romania, our country, and Hungary, for their common history and endeavours to improve healthcare quality in their systems [ 23 ] and France, as a country with one of the best social health insurance systems [ 22 ]. Second, we included two other advanced European countries with different health systems, covering health services through a decentralised national health system: Spain and a Scandinavian country, Finland, where “pharmacists also play an enhanced role in health promotion and disease prevention, including in rural areas” [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…Because pharmacy good practices aim to provide quality services and improve the professional performance of pharmacists [ 21 ], we agreed to include countries based on the latest OECD assessments of the quality and performance of health systems, which also evaluated pharmacists as health service providers [ 22 , 23 ]. According to OECD, the most used systems for covering health services are social health insurance systems and national health systems, but many countries combine those sources with “additional health coverage through voluntary private health insurance” [ 22 ].…”
Section: Introductionmentioning
confidence: 99%